Chemical constituents and anti-ulcer effects of a wild pear (Pyrus syriaca Boiss.): Phytochemical, histopathological and apoptotic approaches - Khaled Abdul-aziz Ahmed; Shatha Nasih Tawfeeq; Sheylan Salah Abdullah; Goran Noori Saleh; Ahmed Aj. Jabbar; Abdulmohsen I. Algefare; Manal A. Alfwuaires; Muzhda Haydar Saber; Mustafa Abdul-Monam Zainel; Talal Salem Al-Qaisi; Ahlam Dhafer Alshehri; Hanan Ibrahim Alsharif; et al. (PLoS ONE, 2026)
Gastric ulcers are a major health concern that can cause severe complications such as bleeding (perforation), digestive blockage, or even stomach cancer if not treated properly. In this study, we evaluated the phytoconstituents, acute toxicity, and gastroprotective potential of the unexplored Pyrus syriaca Boiss. in ethanol-mediated gastric ulcer in rats. Experimental rats were housed in different cages and fasted before receiving pretreatments (250 and 500 mg/kg) and absolute ethanol (5 mL/kg, i.g.) administration. Phytochemical investigations unveiled increased phenolic (142.55 GAE/100 g), flavonoid (73.65 QE/100 g), and anthocyanins (44.05 CGE/100 g) in methanolic extracts of Pyrus syriaca (MEPS). The toxicity evaluation of MEPS (2 and 5 g/kg) did not show any behavioral or physiological changes in rats, even after 14 days of trial. The in vivo gastroprotective evaluation of MEPS (250 and 500 mg/kg) showed a dose-related protection against ethanol-mediated ulceration comparable to lansoprazole. MEPS pretreatment (250 and 500 mg/kg) improved gastric defense barriers (mucus content and pH maintenance) as well as ameliorated gastric tissue alterations, lowering ulcer index areas by 22.13% and 50.40%, respectively. Interestingly, MEPS exhibited significant antioxidant and anti-inflammatory potentials, denoted by up-regulated superoxide dismutase, catalase, interleukin (IL-10), while lowering MDA, TNF-α, and IL-6 cytokines. The anti-apoptotic effects of MEPS were confirmed by down-regulated Bax (by 35.29%, and 47.05%, respectively) and increased Bcl-2 expressions (by 51.42% and 60%, respectively). Collectively, P. syrica showed enriched phytoconstituents that supported its gastroprotective potentials through modulation of antioxidant, inflammatory, and apoptotic cascades.